Pengaruh Disiplin Kerja dan Motivasi Terhadap Kinerja Pegawai pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kabupaten Toraja Utara - Riska Yanti; Rati Pundissing; Randi Tangdialla (CV. Ulil Albab Corp, 2024)
The aim of this research is to find out whether there is an influence of work discipline and motivation on employee performance at the North Toraja Regency DPMPTSP. The data collection procedures for this research are: observation, questionnaires and documentation. The method used in this research is the Quantitative Method using the Multiple Linear Regression method and processed using SPSS 26. This research was conducted at the Toraja Regency Investment and One Stop Integrated Services Service (DPMPTSP), with a sample size of 38 respondents. The technique that researchers used in sampling was a saturated sampling technique. The results of calculations using the t test on the work discipline variable t count > t table with a value of (3.273) > (1.690) and on the motivation variable t count > t table with a value of (9.184) > (1.690). The conclusion of this research is that work discipline and motivation have a positive and significant effect on employee performance at the Toraja Regency Investment and One-Stop Integrated Services Service (DPMPTSP).